2018
DOI: 10.1186/s12913-018-3643-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and utilization of family planning methods among people living with HIV in Kathmandu, Nepal

Abstract: BackgroundAddressing family planning (FP) needs of people living with HIV is an effective response to HIV prevention. Healthy timing and spacing of births help ensure the health and well-being of all women and infants, regardless of their HIV-infection. In addition, preventing unintended pregnancies is an important strategy for prevention of mother to child transmission of HIV. The main purpose of this study was to explore the knowledge of family planning methods and identify factors affecting the utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The literature identified multiple factors affecting the use of modern FP. Women’s age, 16 , 21 , 25 , 27 , 32 , 33 level of educational attainment, 18 , 21 , 24 , 26 , 28 , 29 , 33 , 34 marital status, 25 , 31 , 35 level of earnings, and wealth status 21 , 25 , 33 , 36 are the factors associated with modern FP method use. Likewise, studies showed having information or knowledge of modern FP, 21 , 30 , 36 – 38 knowledge of HIV-positive status, 39 attitude held by women toward modern FP 21 , 30 is the determinant of modern FP use by women.…”
Section: Introductionmentioning
confidence: 99%
“…The literature identified multiple factors affecting the use of modern FP. Women’s age, 16 , 21 , 25 , 27 , 32 , 33 level of educational attainment, 18 , 21 , 24 , 26 , 28 , 29 , 33 , 34 marital status, 25 , 31 , 35 level of earnings, and wealth status 21 , 25 , 33 , 36 are the factors associated with modern FP method use. Likewise, studies showed having information or knowledge of modern FP, 21 , 30 , 36 – 38 knowledge of HIV-positive status, 39 attitude held by women toward modern FP 21 , 30 is the determinant of modern FP use by women.…”
Section: Introductionmentioning
confidence: 99%
“…Only 11 % of either the respondents or their partner had used the emergency contraceptive pill whereas, in Thailand as per the cohort study 29.6% had used the dual protection (30). In the similar study done in Kaski district of Nepal, 0.83% had used it (5).…”
Section: Utilization Of the Family Planning Methodsmentioning
confidence: 89%
“…This indicates the need of sufficient counselling and awareness to the PLHIV. A similar study done in Kaski resulted the significant association between counselling sessions on family planning and the use of them (5). However according to the studies done in Ghana and Uganda misinformation, fear of side effects, negative perceptions, health concerns, reduction in pleasure were identified as the reason for non-utilization of the family planning (32,33).…”
Section: Perceived Reasons For Not Using Family Planning Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Many studies has shown that sexuality education is key in prevention of HIV and related sexually transmitted diseases especially if given to adolescents, schools and many people those that receive sex education are likely not to indulge in risky sexual behaviours [8,9]. HIV testing and counselling is so important because it helps to identify those having HIV making it easier for treatment especially home based HIV counselling and testing and also prevent mother-to-child transmission (MTCT) this should also be coupled with counselling about family planning methods other than condom use alone [10][11][12][13] and which lowers transmission to others however some studies found that people are scared to find out their status, shy, fear what people might say about them in case they are positive and above all fear of death [14]. There is much evidence that a higher level of education is correlated with having more knowledge about HIV risk when compared with populations of lower education and in such categories transmission of HIV is lower in highly educated as compared to the counterparts [15].…”
Section: Introductionmentioning
confidence: 99%